INTEGRATION OF ENTERPRISE VALUES IN CIVIC EDUCATION EFFORTS TO ESTABLISH ECONOMIC CIVIC IN SENIOR HIGH SCHOOL 1 SUNGAI RAYA, KUBU RAYA DISTRICT`S - Rube’i, Muhammad Anwar (Department of Civic Education, 2014)
The study entitled